PERAN KARAKTERISTIK KEPRIBADIAN, LEADER MEMBER EXCHANGE, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT.MATAHARI SILVERINDO JAYA (MSJ) SEMARANG - Muhaimin .; Kunartinah .; Kis Indriyaningrum (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2011)
This study aimed to determine the effect of personality characteristics, leader member exchange and work environment on performance. To analyze the effect, the data were analyzed using a quantitative analysis of themultiple linear regression. The results showed that the characteristics of personality (Big Five Personality) did not affect positively and significantly. While the leader member exchange and work environment is positive andsignificant. The results of the model test study